Advanced cancer and concomitant dementia: access to specialized palliative care, emergency room, hospital care, and place of death. (3rd July 2022) - Fürst, Per; Strang, Peter; Hedman, Christel; Schultz, Torbjörn
Abstract: Background: Dementia and advanced cancer are complex, life-limiting conditions that benefit from specialized palliative care (SPC) interventions at the end of life. The objective was to study possible differences in care for patients with concomitant advanced cancer and dementia (CA-DEM) or cancer only (CA) regarding access to SPC, acute hospital care, and place of death. Materials and methods: A retrospective observational registry study on health care consumption data from the Stockholm Regional Council involving logistic regression analyses of age, sex, living arrangements, comorbidities, dementia diagnosis, and socio-economic status. Results: Of the 12, 667 persons aged ≥65 years who died from advanced cancer between 2015 and 2019, 605 had concomitant dementia. Of these, 76% of patients with CA and 42% of patients with CA-DEM had access to SPC ( p <.0001). There were more admissions to palliative care for persons not living in nursing homes ( p <.0001), women ( p <.0001), socioeconomically privileged patients ( p <.05), those with fewer comorbidities ( p <.0001), and younger patients (<85 years) ( p <.0001). Access to SPC reduced ER visits, hospitalizations, and acute hospital deaths for CA, whereas access to SPC only reduced hospital deaths in the CA-DEM group. Conclusions: The probability of being admitted to SPC was lower in cancer patients with known dementia. Access to SPC reduced emergency room visits and acute admissions to hospitals for the whole group, and hospital deaths both for CA and CA-DEM.